Pelatihan dan Pendampingan Masyarakat melalui Kegiatan Cooking Class di Desa Aan Klungkung - Ni Wayan Mekarini; I Made Agung Rai Antara; Km Shintiya Nita Kristina Putri; I Made Sunata; I Kadek Agus Endrawan (Pubfine Media Group, 2024)
Aan Village with their three main tourist attractions, including the Secret Waterfall, Petapan Park with its bathing garden, and Bukit Kembar, the potential twin hills. Visitors who have enjoyed climbing down the waterfall cliff feel thirsty and hungry, but the warung (cafee) in the object has not provided food for foreign guests need. Even though guests are satisfied with the beauty and uniqueness of the object, the food provided at the object is very limited and it is difficult for guests to enjoy it. Therefore, it is seemed necessary to hold cooking class training that focuses on western food as a solution to avoid guest disappointed. The team took coordination with the object management, Pokdarwis and the PKK women's group for the implementation of the training which was determined to be held at the Aan village traditional hall. Activities are carried out in 4 stages, namely the preparation stage, cooking demonstration, assistance and enjoying the dishes. The participants were very enthusiastic in participating in each stage. This cooking demonstration training activity is a form of support in optimizing the tourist village and the contribution of the students of Faculty of Business and Tourism Triatma Mulya University who took KKNT in Aan village. The training on making dishes with the theme Western Dishes aims to provide knowledge of western cuisine menus, presentation skills, and as a business opportunity for PKK women’s group in Aan village. With the full attention given, the team believed that participants will be able to absorb knowledge, skills and apply them to their respective families. Moreover, the team shared cooking tips and responded well to each of the participants' questions. At the end of the activity, the head of Aan PKK women’s group expressed her happiness over this activity and hoped that similar training activities could be hold then.